RISK ANALYSIS ON MSME TATTI CROCHET USING HOUSE OF RISK - Ramadhani, Anisa Ramadhani; Achmadi, Fuad; Laksmana, Dimas Indra (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2022)
Tatti Crochet is an MSME (Micro, Small, and Medium Enterprise) in Malang City engaged in the handicraft industry. The handicrafts produced are knitted goods, with a specialisation in knitting bags. As an MSME producing handicrafts, Tatti Crochet faces problems in human resources, especially knitters. The number of knitters currently available is three people, and this number cannot support the production needs of Tatti Crochet. This is one of the risks that must be faced not only by MSMEs but also by other organisations and companies. Risk management can be carried out by risk identification, evaluation and measurement, and risk management. One method that can be used to manage risk is the House of Risk. From the risk identification process, Tatti Crochet faced 22 risk events triggered by 29 agents. Based on the calculation of HOR Phase 1, 10 risk agents will enter HOR Phase 2 for determining preventive action, namely A11, A10, A18, A13, A14, A3, A12, A5, A28, and A4. Finally, one preventative measure was soon done with the highest ETD number, PA1, with ETD 1620.